Allosteric control of the exportin CRM1 unraveled by crystal structure analysis. (6th June 2014) - Monecke, Thomas; Dickmanns, Achim; Ficner, Ralf
<x xml:space="preserve">Abstract</x> Nucleocytoplasmic trafficking in eukaryotic cells is a highly regulated and coordinated process which involves an increasing variety of soluble nuclear transport receptors. Generally, transport receptors specifically bind their cargo and facilitate its transition through nuclear pore complexes, aqueous channels connecting the two compartments. Directionality of such transport events by receptors of the importin β superfamily requires the interaction with the small GTPase Ras‐related nuclear antigen (Ran). While importins need RanGTP to release their cargo in the nucleus and thus to terminate import, exportins recruit cargo in the RanGTP‐bound state. The exportin chromosome region maintenance 1 (CRM1) is a highly versatile transport receptor that exports a plethora of different protein and RNP cargoes. Moreover, binding of RanGTP and of cargo to CRM1 are highly cooperative events despite the fact that cargo and RanGTP do not interact directly in crystal structures of assembled export complexes. Integrative approaches have recently unraveled the individual steps of the CRM1 transport cycle at a structural level and explained how the HEAT‐repeat architecture of CRM1 provides a framework for the key elements to mediate allosteric interactions with RanGTP, Ran binding proteins and cargo. Moreover, during the last decade, CRM1 has become a more and more appreciated target for anti‐cancer drugs. Hence, detailed understanding of the flexibility, the regulatory features and the positive binding cooperativity between CRM1, Ran and cargo is a prerequisite for the development of highly effective drugs. Here we review recent structural advances in the characterization of CRM1 and CRM1‐containing complexes with a special emphasis on X‐ray crystallographic studies.